Q: What is 4t-6 when t equals -6?

Write your answer...

Submit

Related questions

1.5

24 = t + 624 - 6 = t +6 - 618 = t

2.86 + t = 6t = 6 - 2.86t = 3.14

T = 3x + 7y; x = 4; y = 6T = 3x + 7y (substitute 4 for x, and 6 for y)T = 3(4) + 7(6) = 12 + 42 = 54

6 points in a touchdown

24 = T + 6 take 6 from each side and you get: 24 - 6 = T therefore 18 = T

0.8333

Yep.

9t+6, but you would need answer to t or you would need the answer to the equation

6 Points for a Touchdown (in American Football)

6 Players in a Hockey Team

6 Pockets on a Snooker Table

-24

I am assuming that k is the constant of proportionality so that f = k*a*t/b2 = 3*4*6/22 = 18

-47

t= -6

If A = T and T = U then A = U.

4t = 24 Therefore t = 24/4 t = 6

6t 6(2) t=2 12 The answer is 12.

Yes and t = 1 in both equations

i don´t know i´m asking you

2t-6=3-t 3t-6=3 Add t to both sides 3t=9 Add 6 to both sides t=3 Divide both sides by 3

6 oz = 3/4 C = 12 T = 36 t

S = 3 st + 3t = 6 st = 6 - 3t s = (6 - 3t)/t = 6/t - 3

I'd guess at the word tzitzi like the sauce.

People also asked